On Milnor classes of constructible functions - Silva, Mauri Pereira da (2019)
The main goal of this thesis is to present a generalization of the important invariant of the singularity theory, called the Milnor number. Such generalization is what we call the logarithmic Milnor number. As well as to discuss about more general de nitions in the context of constructible functions, presenting observations, examples and properties. Among the concepts we work on are also the Fulton-Johnson class, the SchwartzMacPherson class, the Milnor class and the Segre class.